Explicit Calculations of Wet‐Bulb Globe Temperature Compared With Approximations and Why It Matters for Labor Productivity. Issue 3 (4th March 2022) - Kong, Qinqin; Huber, Matthew
Abstract: Wet‐bulb globe temperature (WBGT) is a widely applied heat stress index. However, most applications of WBGT within the heat stress impact literature that do not use WBGT at all, but use one of the ad hoc approximations, typically the simplified WBGT (sWBGT) or the environmental stress index (ESI). Surprisingly, little is known about how well these approximations work for the global climate and climate change settings that they are being applied to. Here, we assess the bias distribution as a function of temperature, humidity, wind speed, and radiative conditions of both sWBGT and ESI relative to a well‐validated, explicit physical model for WBGT developed by Liljegren, within an idealized context and the more realistic setting of ERA5 reanalysis data. sWBGT greatly overestimates heat stress in hot‐humid areas. ESI has much smaller biases in the range of standard climatological conditions. Over subtropical dry regions, both metrics can substantially underestimate extreme heat. We show systematic overestimation of labor loss by sWBGT over much of the world today. We recommend discontinuing the use of sWBGT. ESI may be acceptable for assessing average heat stress or integrated impact over a long period like a year, but less suitable for health applications, extreme heat stress analysis, or as an operational index for heat warning, heatwave forecasting, or guiding activity modification at the workplace. Nevertheless, Liljegren's approach should be preferred over these ad hoc approximations and we provide a fast Python implementation to encourage its widespread use. Plain Language Summary: Wet‐bulb globe temperature (WBGT) is a widely applied heat stress index. However, most applications of WBGT within the climate change heat stress impact literature that do not use WBGT at all but use one of the ad hoc approximations, typically the simplified WBGT (sWBGT) or sometimes the environmental stress index (ESI). But we know little about how well these approximations work for measuring heat stress. Here, we evaluate the performance of sWBGT and ESI against a well‐validated, explicit physical model of WBGT. sWBGT greatly overestimates heat stress under a hot, humid climate. ESI performs much better in measuring average heat stress. But they both may seriously underestimate severe heat stress, especially in hot, dry regions. Our results suggest that previous studies using sWBGT tend to dramatically overestimate heat stress and its economic and health implications, which may further misinform policymaking. We recommend discontinuing the use of sWBGT. ESI may be acceptable for assessing average heat stress, but less suitable for the warning or forecasting of extreme heat, or providing guidance for dealing with workplace heat stress. Nevertheless, the well‐validated physical model of WBGT should be preferred over these approximations and we provide a Python implementation to encourage its widespread use. Key Points: We evaluate biases of two common approximations to Wet‐bulb globe temperature (WBGT) in comparison with explicitly calculated WBGT and consider labor implications Simplified WBGT generally overestimates heat stress and resulting labor loss, whereas environmental stress index is less biased. Both methods underestimate peak heat stress Both methods are systematically biased. We offer a computationally efficient Python implementation to encourage accurate WBGT calculations